Human growth hormone - Çoker, Ajda; Arman, Ahmet (İstanbul Kültür Üniversitesi, 2009)
Growth hormone (GH), is expressed from anterior pituitary gland as a 191 amino acid long polypeptide hormone, has essential role on postnatal growth. In addition to longitudinal growth, GH has various effects on carbohydrate, lipid, protein and mineral metabolisms. GH is expressed from GH-N gene which is located within the GH gene cluster consisting three chorionic somatomammotropin (CS) and GH-V genes on chromosome 17q22-24. Secretion of GH is under control of hypothalamic hormones; somatostatin (SRIF) and growth hormone releasing hormone (GHRH). GH shows it’s biological activities by binding to growth hormone receptor (GHR). After dimerization of GHR, JAK2 is associated with GHR and activated, and JAK2 phosphorylates itself, GHR, signal transducer and activator of transcription (STAT) and intracellular proteins. Activated STAT dimers enter into nucleus, bind to promoter of the target genes such as Spi and activate transcription. Also, RAS/MAPK and PKC signal transduction pathways are known to take role in GH signaling. GH signaling is negatively controlled by SHP via the reduction of intracellular Ca++ levels and also suppressors of cytokine signaling (SOC) with dephosphorilation of JAK2.
Keywords: Growth; growth hormone; growth hormone receptor; signal transduction.